The Gown Must Go To Town. (April 2016) - Essel, Osuanyi Quaicoo
Abstract: This article reviews the "The Gown Must Go to Town" exhibition staged in the Museum of Science and Technology, Accra, highlighting its theme as well as the Afrocentric philosophical messaging of the exhibits. Centered on the dynamism of the city, the exhibits carried conceptual information tailored to comment on the disastrous environmental consequences of the twenty‐first century inventive technological hardware, fibers, and plastic waste (and its mismanagement) that plagues the city. It made powerful visual statements, in an artistic way, of how to control these problems. However, I argue that because of the limitations placed on Ghana, Ghanaian art should pay more focused attention on industrial art instead of conceptual art. This review by no means brands conceptual art as inferior to industrialized art, but it maintains that it is through a focus on industrial art that the nation could meet its own functional and decorative needs, and cease doing so by extensive importation. This argument is based on the fact that conceptual art took its root from Africa in a non‐academic format that has long been practiced in the continent for centuries, and therefore not an emergent art in the African artistic milieu—as it is perceived to be.